Liquid alloy-loaded carbon nanotube composite material and preparation method thereof, and positive electrode material of sodium-sulfur electrode and preparation method thereof
Through the carbon nanotube composite material loading liquid alloy, the porous structure of gallium-bismuth-molybdenum liquid alloy and carbon nanotubes is used to solve the problem of poor sulfur utilization and circulation performance in sodium-sulfur batteries, and more efficient electricity Chemical reactions and stability.
Patent Information
- Application Number
- CN202311167216.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
Sodium-sulfur batteries have problems such as shuttle effect and volume expansion due to the insulation of sulfur and the easy soluble polysulfides in electrolyte, resulting in low sulfur utilization and poor circulation performance, which affects the electrochemical performance.
Carbon nanotube composite material with liquid alloy is used to inhibit the shuttle effect and sodium sulfide solid growth through the carbon nanotube gallium-bismuth-molybdenum liquid alloy, thereby improving the conversion power and utilization of active substances, and using carbon nanotubes to provide porous space and physical adsorption to improve circulation stability.
It significantly improves the kinetics and cycle stability of sodium-sulfur batteries, and improves the utilization rate and electrochemical performance of sulfur.
Smart Images

Figure CN119133449A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for sodium-sulfur batteries, and in particular to a liquid alloy-loaded carbon nanotube composite material and a preparation method thereof, and a positive electrode material for a sodium-sulfur electrode and a preparation method thereof. Background Art
[0002] Energy is an indispensable material foundation for human development and a solid guarantee for the economic diversification of various countries. It has immeasurable strategic significance for the national economy and people's livelihood. In recent years, global oil consumption has decreased by 9.3%, the largest decline in history. Renewable energy has increased by 9.7%, and has continued to develop at a rapid pace. The demand for oil and gas has been increasingly challenged, but it still cannot shake the dominant position of fossil fuels in the energy system. However, under the influence of political environments such as crude oil production cuts and international regional conflicts, oil prices have been rising all the way, and the contradictions on the global oil and gas supply and demand have become more intense, indicating that the transformation of the energy structure is imminent. New energy technologies have a huge potential market and can create huge economic opportunities.
[0003] As we all know, the most widely used battery at present is the lithium-ion battery. However, the theoretical energy density of traditional lithium-ion batteries is about 387Wh / kg, which limits their wide application in power vehicles and pure electric vehicles. Lithium-sulfur batteries have attracted widespread attention because of the theoretical energy density of sulfur as high as 2500Wh / kg and the theoretical specific capacity as high as 1675mAh / g. Sulfur has the advantages of low cost, non-toxicity and good safety. However, due to the scarcity of lithium in the earth's crust, it only accounts for about 0.0065% and is expensive, while sodium accounts for about 2.64%. The electrode potential of sodium is -2.71V, slightly higher than lithium's -3.02V, and is safer. Moreover, sodium and lithium are in the same main group and have similar electrochemical properties, so sodium can be used to replace lithium to construct sodium-sulfur batteries.
[0004] However, since metallic sodium is more active than lithium, sodium-sulfur batteries face more challenges than lithium-sulfur batteries, especially in terms of the utilization of sulfur active materials and capacity retention during cycling. Similar to lithium-sulfur batteries, when room temperature sodium-sulfur batteries use liquid electrolytes, due to the insulation of sulfur, polysulfides are easily soluble in the electrolyte, resulting in shuttle effects, volume expansion, etc., resulting in low sulfur utilization and poor cycle performance, which seriously affects the electrochemical performance of sodium-sulfur batteries. Summary of the invention
[0005] The present invention provides a liquid alloy-loaded carbon nanotube composite material, wherein the carbon nanotubes and the liquid alloy ensure the overall electrical conductivity of the material, and the composite material as a whole is loose and porous, providing sufficient space for the loading of sulfur, and the gallium-bismuth-molybdenum liquid alloy can effectively inhibit the shuttle effect and the growth of sodium sulfide solids, thereby significantly improving the conversion power and actual utilization rate of active substances in sodium-sulfur batteries.
[0006] In order to solve the above technical problems, the present invention provides a liquid alloy-loaded carbon nanotube composite material, comprising liquid alloy and carbon nanotubes, wherein the liquid alloy is uniformly adsorbed on the carbon nanotubes, and the liquid alloy comprises gallium metal, bismuth metal and molybdenum metal.
[0007] The above-mentioned carbon nanotube composite material loaded with liquid alloy is a sulfur catalyst with efficient catalytic effect. Carbon nanotubes are used to load gallium-bismuth-molybdenum liquid alloy. During the cycle, since the gallium-bismuth-molybdenum phase is in liquid state, it can more fully contact with the polysulfide produced during the reaction process, thereby generating interaction and achieving an effective shuttling effect inhibition effect. At the same time, the presence of gallium-bismuth-molybdenum liquid alloy can inhibit the agglomeration growth of sodium sulfide solids, thereby preventing it from losing electrochemical reaction activity due to low conductivity. Due to the presence of multiple metal atoms in gallium-bismuth-molybdenum liquid alloy, it presents an uneven electron distribution and exhibits strong catalytic activity, thereby improving the redox reaction kinetics of sodium-sulfur batteries. Carbon nanotubes provide loading space for gallium-bismuth-molybdenum liquid alloys during material synthesis. In subsequent applications, carbon nanotubes can also inhibit the dissolution of polysulfides through physical adsorption and improve the cycle stability of sodium-sulfur batteries.
[0008] In a preferred or optional embodiment, the liquid alloy contains gallium metal, bismuth metal, and molybdenum metal in a mass ratio of (80-90):(5-10):(5-10).
[0009] In a preferred or optional embodiment, the mass ratio of the liquid alloy to the carbon nanotubes is (5-10):(1-3).
[0010] The present invention also provides a method for preparing a liquid alloy-loaded carbon nanotube composite material, which is used to prepare the liquid alloy-loaded carbon nanotube composite material. The preparation steps are as follows:
[0011] S100: preparing gallium metal, bismuth metal, and molybdenum metal, mixing them, heating and melting them, and obtaining a liquid alloy material;
[0012] S200: adding liquid alloy material and carbon nanotubes into isopropanol, mixing them evenly, and then heating to volatilize the isopropanol to obtain a carbon nanotube composite material loaded with liquid alloy.
[0013] By means of the above preparation method, a liquid alloy-loaded carbon nanotube composite material can be efficiently prepared. The liquid alloy material can be evenly loaded on the carbon nanotubes under the influence of isopropanol, and then the pure liquid alloy-loaded carbon nanotube composite material can be obtained by volatilizing the isopropanol.
[0014] In a preferred or optional embodiment, in step S100, the heating temperature of the heating and melting is controlled to be 50° C.-90° C., and the heating time is 1 h-3 h.
[0015] In a preferred or optional embodiment, in step S200, the mass ratio of the liquid alloy material to isopropanol is (0.5-1):(78.55-235.55).
[0016] In a preferred or optional embodiment, in step S200, the liquid alloy material and carbon nanotubes are added to isopropanol, and ultrasonic mixing is continued for 1 h to 3 h to achieve uniform mixing, and then heating is carried out at a temperature of 70° C. to 95° C. and stirring is continued until the isopropanol is completely volatilized to obtain a carbon nanotube composite material loaded with liquid alloy.
[0017] The present invention also provides a positive electrode material for a sodium-sulfur electrode, comprising the above-mentioned carbon nanotube composite material loaded with liquid alloy and nano-sulfur, wherein the nano-sulfur is doped in the carbon nanotube composite material loaded with liquid alloy.
[0018] In the positive electrode material of the above sodium-sulfur electrode, the introduction of carbon nanotubes and liquid alloys ensures the conductivity of the overall electrode and can achieve rapid electron transfer during the charge and discharge reaction. On the other hand, the overall porous carbon nanotube composite material loaded with liquid alloy can provide sufficient space for the loading of nano-sulfur, and can also alleviate the volume expansion of nano-sulfur during the charge and discharge process, thereby improving the cycle stability of the electrode.
[0019] In a preferred or optional embodiment, the mass ratio of the liquid alloy-loaded carbon nanotube composite material to the nano-sulfur is (0.9-1.1):(2-5).
[0020] The present invention also provides a method for preparing a positive electrode material of a sodium-sulfur electrode, which is used to prepare the positive electrode material of the sodium-sulfur electrode, and the preparation steps are as follows:
[0021] S300: adding the liquid alloy-loaded carbon nanotube composite material and nano-sulfur into a ball mill, and mixing them for 3h-5h at a rotation speed of 500r / min-800r / min using a ball mill to obtain a ball milled mixture;
[0022] S400: In a nitrogen environment, heat-treating the ball-milled mixture at a temperature of 100° C. to 200° C. for 5 h to 24 h to obtain a positive electrode material for a sodium-sulfur electrode.
[0023] The positive electrode material of the sodium-sulfur electrode can be effectively prepared by the above preparation method. The nano-sulfur and the carbon nanotube composite material loaded with liquid alloy are uniformly mixed under the action of a ball mill. At the same time, the ball mill can also make the nano-sulfur enter the gap of the carbon nanotube composite material loaded with liquid alloy. Then, the sulfur and the carbon nanotube composite material loaded with liquid alloy are firmly connected through high-temperature heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the liquid alloy-loaded carbon nanotube composite material prepared in Example 1 of the present invention;
[0025] Figure 2 This is a discharge specific capacity cycle diagram of the positive electrode material of the sodium-sulfur electrode prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0027] Example 1
[0028] This embodiment provides a method for preparing a liquid alloy-loaded carbon nanotube composite material, and the specific preparation steps are as follows:
[0029] S100: commercially available gallium, bismuth and molybdenum metals are mixed in a weight ratio of 90:8:2, and then the mixed metals are placed on a heating plate and heated at 80° C. for 2 hours to obtain a liquid alloy material;
[0030] S200: Take 0.5 g of liquid alloy material and 0.1 g of commercially available carbon nanotubes, place them in 150 mL of isopropanol, continue ultrasonication for 2 h, and then heat at 80° C. and continue stirring until the isopropanol is completely evaporated to obtain a liquid alloy-loaded carbon nanotube composite material.
[0031] Example 2
[0032] This embodiment provides a method for preparing a positive electrode material of a sodium-sulfur electrode, and the specific preparation steps are as follows:
[0033] S300: putting the liquid alloy-loaded carbon nanotube composite material prepared in Example 1 and the pure phase nano-sulfur powder into a ball mill at a mass ratio of 1:3, and mixing them for 4 hours using a planetary ball mill at a rotation speed of 600 r / min to obtain a ball milled mixture;
[0034] S400: The ball-milled mixture is placed in a tubular furnace under nitrogen protection and heat treated at 150°C for 12 hours to obtain the positive electrode material of the sodium-sulfur electrode.
[0035] Example 3
[0036] This embodiment provides a method for preparing a liquid alloy-loaded carbon nanotube composite material, and the specific preparation steps are as follows:
[0037] S100: Mix commercially available gallium, bismuth and molybdenum metals in a weight ratio of 80:10:10, and then place the mixed metals on a heating plate and heat at 95° C. for 3 hours to obtain a liquid alloy material;
[0038] S200: Take 1 g of liquid alloy material and 0.3 g of commercially available carbon nanotubes, place them in 300 mL of isopropanol, continue ultrasonication for 3 h, and then heat at 95° C. and continue stirring until the isopropanol is completely volatilized to obtain a carbon nanotube composite material loaded with liquid alloy.
[0039] Example 4
[0040] This embodiment provides a method for preparing a positive electrode material of a sodium-sulfur electrode, and the specific preparation steps are as follows:
[0041] S300: putting the liquid alloy-loaded carbon nanotube composite material prepared in Example 3 and the pure phase nano-sulfur powder into a ball mill at a mass ratio of 1:5, and mixing them for 5 hours using a planetary ball mill at a rotation speed of 800 r / min to obtain a ball milled mixture;
[0042] S400: The ball-milled mixture is placed in a tubular furnace under nitrogen protection and heat treated at 200°C for 24 hours to obtain the positive electrode material of the sodium-sulfur electrode.
[0043] Example 5
[0044] This embodiment provides a method for preparing a liquid alloy-loaded carbon nanotube composite material, and the specific preparation steps are as follows:
[0045] S100: commercially available gallium, bismuth and molybdenum metals are mixed in a weight ratio of 90:5:5, and then the mixed metals are placed on a heating plate and heated at 50° C. for 1 hour to obtain a liquid alloy material;
[0046] S200: Take 0.5 g of liquid alloy material and 0.3 g of commercially available carbon nanotubes, place them in 100 mL of isopropanol, continue ultrasonication for 1 hour, and then heat at 70°C and continue stirring until the isopropanol is completely evaporated to obtain a liquid alloy-loaded carbon nanotube composite material.
[0047] Example 6
[0048] This embodiment provides a method for preparing a positive electrode material of a sodium-sulfur electrode, and the specific preparation steps are as follows:
[0049] S300: putting the liquid alloy-loaded carbon nanotube composite material prepared in Example 5 and the pure phase nano-sulfur powder into a ball mill at a mass ratio of 1:2, and mixing them for 3 hours using a planetary ball mill at a rotation speed of 500 r / min to obtain a ball milled mixture;
[0050] S400: The ball-milled mixture is placed in a tubular furnace under nitrogen protection and heat treated at 100°C for 8 hours to obtain the positive electrode material of the sodium-sulfur electrode.
[0051] Performance Testing
[0052] The liquid alloy-loaded carbon nanotube composite material prepared in Example 1 was examined by scanning electron microscopy, and the obtained scanning electron microscopy image is as follows: Figure 1 As shown in the figure, it can be seen that the liquid alloy is loaded on the carbon nanotubes. The positive electrode material of the sodium-sulfur electrode prepared in Example 2 was tested for discharge specific capacity. The test results are as follows: Figure 2 As shown in the figure, it can be seen that after multiple cycles of the positive electrode material of the sodium-sulfur electrode in the present application, the decrease in discharge specific capacity is small and it still has a good discharge specific capacity.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A liquid alloy-loaded carbon nanotube composite material, characterized in that: It comprises liquid alloy and carbon nanotubes. The liquid alloy is uniformly adsorbed on the carbon nanotubes. The liquid alloy comprises gallium metal, bismuth metal and molybdenum metal.
2. The liquid alloy-loaded carbon nanotube composite material according to claim 1, characterized in that: The liquid alloy contains gallium metal, bismuth metal and molybdenum metal in a mass ratio of (80-90):(5-10):(5-10).
3. The liquid alloy-loaded carbon nanotube composite material according to claim 1, characterized in that: The mass ratio of the liquid alloy to the carbon nanotubes is (5-10):(1-3).
4. A method for preparing a liquid alloy-loaded carbon nanotube composite material, characterized in that: The preparation steps for preparing the liquid alloy-loaded carbon nanotube composite material according to any one of claims 1 to 3 are as follows: S100: preparing gallium metal, bismuth metal, and molybdenum metal, mixing them, heating and melting them, and obtaining a liquid alloy material; S200: adding the liquid alloy material and carbon nanotubes into isopropanol, mixing them evenly, and then heating to volatilize the isopropanol to obtain the liquid alloy-loaded carbon nanotube composite material.
5. The preparation method according to claim 4, characterized in that: In the step S100, the heating temperature of the heating and melting is controlled to be 50°C-90°C and the heating time is controlled to be 1h-3h.
6. The preparation method according to claim 4, characterized in that: In the step S200, the mass ratio of the liquid alloy material to the isopropanol is (0.5-1):(78.55-235.55).
7. The preparation method according to claim 4, characterized in that: In the step S200, the liquid alloy material and the carbon nanotubes are added to the isopropanol, and ultrasonication is continued for 1 h to 3 h to mix them evenly, and then heating is continued at 70° C. to 95° C. with stirring until the isopropanol is completely volatilized to obtain the liquid alloy-loaded carbon nanotube composite material.
8. A positive electrode material for a sodium-sulfur electrode, characterized in that: The invention comprises the liquid alloy-loaded carbon nanotube composite material according to any one of claims 1 to 3 and nano-sulfur, wherein the nano-sulfur is doped in the liquid alloy-loaded carbon nanotube composite material.
9. The positive electrode material for sodium-sulfur electrode according to claim 8, characterized in that The mass ratio of the carbon nanotube composite material loaded with liquid alloy to the nano-sulfur is (0.9-1.1):(2-5).
10. A method for preparing a positive electrode material for a sodium-sulfur electrode, characterized in that: The positive electrode material for preparing the sodium-sulfur electrode according to any one of claims 8 to 9 is prepared in the following steps: S300: adding the liquid alloy-loaded carbon nanotube composite material and nano-sulfur into a ball mill, and mixing them for 3h-5h at a rotation speed of 500r / min-800r / min using a ball mill to obtain a ball milled mixture; S400: In a nitrogen environment, heat-treating the ball-milled mixture at a temperature of 100° C. to 200° C. for 5 h to 24 h to obtain the positive electrode material of the sodium-sulfur electrode.
